A Mini Review on Therapeutic Potential and Chemical Constituents of Tomato: Chemical Constituents in Tomato (Biological Sciences - PJSIR, 2024)
Tomato is the second most important and generally grown vegetable in the world. It is popular as vegetable in many prepared structures (e.g. ketchup, canned entire or in pieces, puree, sauce, soup, squeeze or sun-dried). Tomato and prepared tomato items are important component of the Mediterranean diet. It is a rich source of minerals and strong antioxidants, which provide good health and prevents us from cardiovascular disorders and diabetic blood pressure. The aim of this review is to evaluate the historical record, uses, potential biological activities and chemical constituents of tomato.